SOME ASPECTS OF QUALITY OF COOKED FROZEN PRAWNS - Pillai, V Krishna; Lekshmy, A (Indian Journal of Fisheries, 2011)
PRAWNS of more than 100 counts to the pound are generally precooked beforefreezing and packing. As in the case of all precooked frozen foods expertcare is required to maintain high quality in cooked frozen prawns also. Atotal bacterial count of 100,000-200,000 per gram muscle is suggested as anarbitrary limit for an acceptable quality of cooked frozen prawn in manycountries (Goresline, 1959). The freshness of raw material, no doubt, decidesto a large extent the quality of the final pack. A raw material ofquestionable freshness may yield a product having off odours and flavour